2016
DOI: 10.4103/2231-0762.178748
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes an inducing factor for dental caries: A case control analysis in Jammu

Abstract: Objective:Diabetes mellitus (DM) is a common chronic disease and it has emerged as a major health-care problem. There are more chances of dentinal caries among diabetics than nondiabetics. DM is responsible for causing ascendancy in the proportion and activity of saliva that impacts the oral health. The objective of the present study is to evaluate the impact of various factors present in saliva on tooth decay amid type-II DM in Jammu.Materials and Methods:The subjects in our analysis comprises of 50 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ). Vaziri et al and Ilgüy et al evaluated type 1 and type 2 diabetics but results for each group were separately reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty‐five articles regarding caries experience among type 1 diabetics were analyzed (Table ). Regarding type 2 diabetes 17 studies were included (Table ). Vaziri et al and Ilgüy et al evaluated type 1 and type 2 diabetics but results for each group were separately reported.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of the studies were conducted in India, eight in the United States, six in Brazil, five in Finland, four each in Portugal, Sweden, and Turkey, two in Lithuania, one each in Belgium, Bosnia and Herzegovina, China, Egypt, Germany, Hungary, Iraq, Jordan, Republic of Kosovo, Kuwait, Libya, Malaysia, Mexico, Spain, Sudan, Thailand, and Uruguay…”
Section: Resultsmentioning
confidence: 99%
“…[22] and Singh et al . [23] have found increase in salivary Streptococcus mutans , decrease in salivary flow rate, and increase in the severity of dental caries.In China, Yang et al . [24] found a correlation between caries status and severity with growth and development retardation in children.…”
Section: Discussionmentioning
confidence: 99%
“…[22] and Singh et al . [23] have found increase in salivary Streptococcus mutans , decrease in salivary flow rate, and increase in the severity of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Diabetes has been associated with oral infections such as periodontitis, dental caries, gingivitis and candidiasis. (5)(6)(7) Several studies have documented the oral microbiota in diabetic patients as well as other patient populations. (8)(9)(10) Sharma and coworkers reported that both Gram positive and Gram negative bacteria are fairly involved in dental diseases and that the prevalence of bacteria increases with severity of disease.…”
Section: Introductionmentioning
confidence: 99%